2019
DOI: 10.21608/jabps.2019.6609.1030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of liquorice extract in asthmatic patients

Abstract: Liquorice is one of the commonly used herbs in the field of medicine due to its pharmacological activities. Among these activities, the anti-inflammatory and antiallergic activities that support its use in asthma. This study included 80 asthmatic patients who were classified into two groups, group 1 (Placebo group) maintained on inhaled corticosteroids (ICs in moderate to high doses) and long-acting beta agonist (LABA) and received starch capsule (500 mg starch) twice daily as placebo and group 2 (active treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…β‐glycyrrhizic acid is a potent anti‐inflammatory compound in licorice that controls inflammation by inhibiting glucocorticoid accumulation and ROS production by neutrophils as strong mediators of tissue inflammation (Parvaiz et al, 2014). In a randomized trial, adding licorice (capsule 500 mg twice daily) to the long‐acting beta‐agonist regimen in chronic stable moderate bronchial asthmatic patients significantly improved Forced Vital Capacity (FVC) % and Forced Expiratory Volume1 (FEV1) (Sadek, Tawfik, Hussein, & Abdelhakeem, 2019). A molecular docking study has demonstrated that glycyrrhizic acid have high binding affinity of −8.0 Kcal/mol and strong inhibitors for M pro of SARS‐CoV2 (Srivastava, Yadav, & Sarkar, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β‐glycyrrhizic acid is a potent anti‐inflammatory compound in licorice that controls inflammation by inhibiting glucocorticoid accumulation and ROS production by neutrophils as strong mediators of tissue inflammation (Parvaiz et al, 2014). In a randomized trial, adding licorice (capsule 500 mg twice daily) to the long‐acting beta‐agonist regimen in chronic stable moderate bronchial asthmatic patients significantly improved Forced Vital Capacity (FVC) % and Forced Expiratory Volume1 (FEV1) (Sadek, Tawfik, Hussein, & Abdelhakeem, 2019). A molecular docking study has demonstrated that glycyrrhizic acid have high binding affinity of −8.0 Kcal/mol and strong inhibitors for M pro of SARS‐CoV2 (Srivastava, Yadav, & Sarkar, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Licorice and glycyrrhizin have also been markedly effective against SARS-CoV(Cinatl et al, 2003;Parvaiz et al, 2014), hepatitis C(Miyake et al, 2002) and upper respiratory tract infection(Yanagawa, Ogura, Fujimoto, Shono, & Okuda, 2004).β-glycyrrhizic acid is a potent anti-inflammatory compound in licorice that controls inflammation by inhibiting glucocorticoid accumulation and ROS production by neutrophils as strong mediators of tissue inflammation(Parvaiz et al, 2014). In a randomized trial, adding licorice (capsule 500 mg twice daily) to the long-acting betaagonist regimen in chronic stable moderate bronchial asthmatic patients significantly improved Forced Vital Capacity (FVC) % and Forced Expiratory Volume1 (FEV1)(Sadek, Tawfik, Hussein, & Abdelhakeem, 2019). A molecular docking study has demonstrated that glycyrrhizic acid have high binding affinity of À8.0 Kcal/mol and strong inhibitors for M pro of SARS-CoV2(Srivastava, Yadav, & Sarkar, 2020).Main pharmacological properties of N. sativa and its chemical constituents are antiviral(Salem & Hossain, 2000), anti-inflammatory, immunomodulatory(Forouzanfar, Bazzaz, & Hosseinzadeh, 2014), andF I G U R E1 HPLC chromatograms of ellagic acid (a), emodin (b), glycyrrhizin (c), apigenin (d) thymoquinone (e) in formulations anti-cough (Hosseinzadeh, Eskandari, & Ziaee, 2008) effects.…”
mentioning
confidence: 99%
“…All symptoms usually disappear with discontinuation of therapy. Many studies report no side effects during the course of treatment [31][32] . Generally the onset and severity of symptoms depend on the dose and duration of licorice intake, as well as individual susceptibility.…”
Section: Side Effectsmentioning
confidence: 99%
“…Chen et al showed the efect of glycyrrhizic acid loaded on PLGA nanoparticles in treating allergic asthma [199]. A clinical study showed that aqueous liquorice extract capsules signifcantly improve pulmonary function tests (increase in FVC% and FEV1%) in asthmatic patients [200].…”
Section: Euphorbia Hirtamentioning
confidence: 99%